Preparation method of nitrogen-doped carbon nanotube-loaded nano-iron and application of nitrogen-doped carbon nanotube-loaded nano-iron in negative electrode of lithium battery
By loading nano-iron on nitrogen-doped carbon nanotubes, the problems of low specific capacity and poor cycle stability of lithium battery anode materials are solved, the specific capacity and capacity retention rate of lithium batteries are improved, and the internal resistance is reduced.
Patent Information
- Application Number
- CN202411257600.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The negative electrode material of lithium batteries has low specific capacity and poor circulation stability, resulting in poor battery performance.
By loading nano -iron on nitrogen doping carbon nanotubes, using the conductivity of carbon nanotubes and the high ratio of nano iron to prevent the reunion and volume expansion of nano iron, and improve the charge and discharge efficiency of lithium batteries.
It improves the specific capacity and capacity retention rate of lithium batteries, reduces internal resistance, and enhances the cycle stability of the battery.
Smart Images

Figure CN119346860A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nitrogen-doped carbon nanotubes and lithium-ion battery negative electrode materials, and specifically relates to a preparation method of nitrogen-doped carbon nanotubes loaded with nano-iron and application thereof in lithium-ion battery negative electrode materials. Background Art
[0002] With the rapid development of modern science and technology, lithium batteries, as an important energy storage device, have always been a hot topic in the field of science and technology for performance improvement and application expansion. The negative electrode material of lithium batteries is one of the key factors affecting their overall performance. Therefore, finding negative electrode materials with high specific capacity and excellent cycle stability is of great significance to improving the performance of lithium batteries.
[0003] As a material with excellent conductivity, high specific surface area and good chemical stability, carbon nanotubes are considered to be a potential conductive agent material. In recent years, there has been an increasing number of studies on modifying carbon nanotubes by doping different elements to improve their electrochemical performance. Among them, nitrogen doping is an effective modification method. The introduction of nitrogen can change the electronic structure of carbon nanotubes, improve their electrochemical activity, and thus improve the performance of lithium batteries. In addition, nano-iron, as a metal material with high specific capacity, has also attracted the attention of researchers. However, nano-iron is prone to agglomeration and volume expansion during the charging and discharging process, resulting in a decrease in battery performance. Therefore, combining nano-iron with carbon nanotubes and using carbon nanotubes as carriers can not only prevent the agglomeration and volume expansion of nano-iron, but also use the excellent conductive properties of carbon nanotubes to improve the charging and discharging efficiency of lithium batteries. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of low specific capacity and poor cycle stability of negative electrode materials of lithium batteries, and to provide a preparation method of nitrogen-doped carbon nanotubes loaded with nano-iron and its application in the negative electrode of lithium batteries. This method can not only prevent the agglomeration and volume expansion of nano-iron, but also utilize the excellent conductivity of carbon nanotubes to improve the capacity retention rate of lithium batteries.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing nitrogen-doped carbon nanotubes loaded with nano-iron, the method comprising:
[0007] (1) dissolving the catalyst in anhydrous ethanol and performing ultrasonic dispersion treatment to obtain a catalyst solution with a concentration of 0.2 to 0.6 g / L; uniformly dropping the catalyst solution onto a designated position of a substrate, placing the substrate with the catalyst solution dropped thereon into a vacuum drying oven to vacuum dry and remove the solvent, thereby obtaining catalyst particles;
[0008] (2) placing the substrate loaded with catalyst particles prepared in step (1) into a tubular furnace and placing it at the air inlet position of the heating zone of the tubular furnace; evacuating the tubular furnace, introducing a hydrogen-argon mixed gas, a carbon source, and a nitrogen source, turning on the heating device of the tubular furnace, and raising the furnace temperature to the reaction temperature at a heating rate of 10°C / min to prepare nitrogen-doped carbon nanotube-loaded nano-iron.
[0009] Furthermore, the method also includes step (3), taking out the cooled substrate from the tube furnace and immersing it in anhydrous ethanol, ultrasonically treating the substrate with an ultrasonic disperser to separate the nitrogen-doped carbon nanotube-loaded nano-iron, centrifuging the ultrasonically treated solution with a centrifuge, collecting the nitrogen-doped carbon nanotube-loaded nano-iron precipitated at the bottom, and drying it.
[0010] Furthermore, in step (1), the catalyst is one or more of iron oxide, γ-iron oxide, ferric nitrate nonahydrate, and ferrocene.
[0011] Furthermore, in step (1), the substrate is one or more of a silicon wafer, nickel foam, and a quartz wafer.
[0012] Furthermore, in step (2), the flow rate of the hydrogen-argon mixed gas is controlled at 80-350 sccm.
[0013] Furthermore, in step (2), the carbon source is one or more of ethylene, acetylene, polyethylene and polypropylene.
[0014] Furthermore, in step (2), the nitrogen source is one or more of urea, melamine, xylene and aniline.
[0015] Furthermore, in step (2), the reaction temperature is 700-950° C., and the reaction time is 15-45 min.
[0016] Furthermore, in step (3), the drying treatment is vacuum drying or freeze drying, which can ensure the dryness and stability of the nitrogen-doped carbon nanotubes loaded with nano-iron.
[0017] An application of nitrogen-doped carbon nanotube-loaded nano-iron prepared by the above preparation method, wherein the nitrogen-doped carbon nanotube-loaded nano-iron is used as a negative electrode conductive agent in a lithium-ion battery; in the negative electrode slurry, the ratio of graphite, SBR, carbon black, CMC, and nitrogen-doped carbon nanotube-loaded nano-iron is 94%: 1.8%: 2.2%: 0.5%~1%: 1%~1.5%.
[0018] The beneficial effects of the present invention compared to the prior art are:
[0019] 1. The present invention proposes a novel lithium battery negative electrode conductive agent of nitrogen-doped carbon nanotubes loaded with nano-iron, and nano-iron is loaded on nitrogen-doped carbon nanotubes through a specific preparation process;
[0020] 2. The internal resistance of the lithium battery prepared by using the conductive agent provided by the present invention is lower. The introduction of nitrogen element improves the electrochemical activity of the conductive agent, making the conductive network composed of carbon nanotubes transmit electrons faster, thereby reducing the internal resistance of the lithium battery.
[0021] 3. The lithium battery prepared by using the conductive agent provided by the present invention has higher specific capacity and capacity retention rate. Combining carbon nanotubes with nano-iron can not only prevent the agglomeration and volume expansion of nano-iron, but also utilize the excellent conductivity of carbon nanotubes and nano-iron to improve the specific capacity and capacity retention rate of the lithium battery.
[0022] 4. The present invention provides a method for preparing nitrogen-doped carbon nanotubes based on nano-iron, which achieves efficient and stable preparation of carbon nanotubes by precisely controlling each link in the preparation process. The method has the advantages of simple operation and stable product quality, and is suitable for large-scale production applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the SEM image of nitrogen-doped carbon nanotubes loaded with nano-iron;
[0024] Figure 2 is the EDS curve of nitrogen-doped carbon nanotubes loaded with nano-iron;
[0025] Figure 3 It is a comparison diagram of the cycle curves of Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the protection scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] The present invention uses a specific preparation process to load nano-iron on nitrogen-doped carbon nanotubes, combining the advantages of both, aiming to improve the performance of lithium battery negative electrode materials. Specifically, the present invention achieves the doping of nitrogen elements and the loading of nano-iron on carbon nanotubes through chemical vapor deposition. At the same time, the conductive agent of the present invention is made into a lithium-ion button battery, and the capacity retention rate is improved to a certain extent. The nitrogen-doped carbon nanotube-loaded nano-iron lithium battery negative electrode material proposed in the present invention is expected to provide a new solution for improving the performance of lithium batteries and expanding the application field.
[0028] Example 1
[0029] 1. Catalyst dispersion treatment:
[0030] Add 2 mg of γ-iron oxide powder to 10 ml of anhydrous ethanol and stir with a magnetic stirrer to fully disperse the γ-iron oxide powder in the ethanol to form a uniform mixture. Then, transfer the mixture to an ultrasonic disperser and disperse it at an ultrasonic frequency of 40 kHz for 30 minutes. Add the dispersed mixture drop by drop onto the silicon wafer, place it in a constant temperature oven at 80°C, and dry it for 30 minutes until the anhydrous ethanol is completely evaporated.
[0031] 2. Preparation of nitrogen-doped carbon nanotubes loaded with nano-iron:
[0032] The dried silicon wafer is placed in the center of the heating zone of the tube furnace, and polypropylene and melamine are placed at the air inlet of the tube furnace as carbon source and nitrogen source, respectively. Subsequently, the tube furnace is evacuated, and then a hydrogen-argon mixture is introduced to normal pressure, and this process is repeated three times to ensure the purity of the atmosphere in the furnace. The furnace temperature is raised to 900°C at a heating rate of 10°C / min. When the furnace temperature reaches 900°C, the temperature is maintained for 45 minutes to react, so that the polypropylene and melamine are vaporized and contact the γ-iron oxide catalyst on the silicon wafer, thereby triggering the growth of carbon nanotubes.
[0033] 3. Collection and treatment of nitrogen-doped carbon nanotubes loaded with nano-iron
[0034] After the furnace temperature drops to room temperature, the silicon wafer is taken out of the tube furnace. The silicon wafer is soaked in a beaker filled with anhydrous ethanol and ultrasonically treated for 10 minutes using an ultrasonic disperser. Finally, the ultrasonically treated solution is centrifuged by a centrifuge to collect the carbon nanotubes precipitated at the bottom. The washed carbon nanotubes are placed in a vacuum drying oven and dried at 60°C to obtain a dried carbon nanotube sample.
[0035] Finally, graphite, SBR, carbon black, CMC, and sample were mixed in a ratio of 94%: 1.8%: 2.2%: 0.5%: 1.5% to prepare negative electrode slurry, which was coated on copper foil to make negative electrode sheets. Lithium iron phosphate, conductive agent, and PVDF were used as positive electrodes and mixed in a certain ratio to make slurry, which was coated on aluminum foil to make positive electrode sheets. A button battery was prepared by combining positive electrode shell, negative electrode shell, positive and negative electrode sheets, diaphragm, gasket, shrapnel, and electrolyte, and its electrochemical performance was tested.
[0036] Through the above steps, this embodiment successfully prepared nitrogen-doped carbon nanotubes loaded with nano-iron (such as Figure 1 , Figure 2 This method has the advantages of simple operation and stable product quality, and is suitable for large-scale production applications.
[0037] Example 2
[0038] 1. Catalyst dispersion treatment:
[0039] Add 2 mg of γ-iron oxide powder to 10 ml of anhydrous ethanol and stir with a high-speed stirrer to fully disperse the γ-iron oxide powder in the ethanol to form a uniform mixture. Then, transfer the mixture to an ultrasonic disperser and disperse it at an ultrasonic frequency of 40 kHz for 30 minutes. Add the dispersed mixture drop by drop onto the silicon wafer, place it in a constant temperature oven at 80°C, and dry it for 30 minutes until the anhydrous ethanol is completely evaporated.
[0040] 2. Preparation of nitrogen-doped carbon nanotubes loaded with nano-iron:
[0041] The dried silicon wafer is placed in the center of the heating zone of the tube furnace, and polypropylene and urea are placed at the air inlet of the tube furnace as carbon source and nitrogen source, respectively. Subsequently, the tube furnace is evacuated, and then a hydrogen-argon mixture is introduced to normal pressure, and this process is repeated three times to ensure the purity of the atmosphere in the furnace. The furnace temperature is raised to 900°C at a heating rate of 10°C / min. When the furnace temperature reaches 900°C, the temperature is maintained for 45 minutes to react, so that polypropylene and melamine are vaporized and contacted with the γ-iron oxide catalyst on the silicon wafer, thereby triggering the growth of carbon nanotubes.
[0042] 3. Collection and treatment of nitrogen-doped carbon nanotubes loaded with nano-iron
[0043] After the furnace temperature drops to room temperature, the silicon wafer is taken out of the tube furnace. The silicon wafer is soaked in a beaker filled with anhydrous ethanol and ultrasonically treated for 10 minutes using an ultrasonic disperser. Finally, the ultrasonically treated solution is centrifuged by a centrifuge to collect the carbon nanotubes precipitated at the bottom. The washed carbon nanotubes are placed in a vacuum drying oven and dried at 60°C to obtain a dried carbon nanotube sample.
[0044] Finally, graphite, SBR, carbon black, CMC, and sample were mixed in a ratio of 94%: 1.8%: 2.2%: 0.5%: 1.5% to prepare negative electrode slurry, which was coated on copper foil to make negative electrode sheets. Lithium iron phosphate, conductive agent, and PVDF were used as positive electrodes and mixed in a certain ratio to make slurry, which was coated on aluminum foil to make positive electrode sheets. A button battery was prepared by combining positive electrode shell, negative electrode shell, positive and negative electrode sheets, diaphragm, gasket, shrapnel, and electrolyte, and its electrochemical performance was tested.
[0045] Comparative Example 1
[0046] The conductive agent was replaced with SUPER-P purchased on the market. Finally, the negative electrode slurry was prepared by mixing graphite, SBR, carbon black, CMC, and sample in a ratio of 94%: 1.8%: 2.2%: 0.5%: 1.5%. The negative electrode slurry was coated on copper foil to make a negative electrode sheet. The positive electrode was made of lithium iron phosphate, conductive agent, and PVDF in a certain ratio and coated on aluminum foil to make a positive electrode sheet. The positive electrode shell, negative electrode shell, positive and negative electrode sheets, diaphragm, gasket, shrapnel, and electrolyte were combined to prepare a button battery, and its electrochemical performance was tested.
[0047] Comparative Example 2
[0048] The conductive agent replaces the acetylene black purchased on the market. Finally, the graphite, SBR, carbon black, CMC, and sample are prepared into negative electrode slurry in a ratio of 94%: 1.8%: 2.2%: 0.5%: 1.5%, and the negative electrode slurry is coated on copper foil to make a negative electrode sheet. The positive electrode is made of lithium iron phosphate, conductive agent, and PVDF in a certain proportion and coated on aluminum foil to make a positive electrode sheet. Combine the positive electrode shell, negative electrode shell, positive and negative electrode sheets, diaphragm, gasket, shrapnel, and electrolyte to prepare a button battery, and test its electrochemical performance.
[0049] Comparative Example 3
[0050] The conductive agent uses graphene purchased on the market. Finally, the negative electrode slurry is prepared by mixing graphite, SBR, carbon black, CMC, and sample in a ratio of 94%:1.8%:2.2%:0.5%:1.5%. The negative electrode slurry is coated on copper foil to make a negative electrode sheet. The positive electrode uses lithium iron phosphate, conductive agent, and PVDF in a certain ratio to make a slurry and coat it on aluminum foil to make a positive electrode sheet. Combine the positive electrode shell, negative electrode shell, positive and negative electrode sheets, diaphragm, gasket, shrapnel, and electrolyte to prepare a button battery, and test its electrochemical properties.
[0051] Comparative Example 4
[0052] The conductive agent uses carbon nanotubes purchased on the market. Finally, graphite, SBR, carbon black, CMC, and samples are prepared into negative electrode slurry in a ratio of 94%: 1.8%: 2.2%: 0.5%: 1.5%, and the negative electrode slurry is coated on copper foil to make a negative electrode sheet. The positive electrode uses lithium iron phosphate, conductive agent, and PVDF in a certain proportion to make a slurry and coat it on aluminum foil to make a positive electrode sheet. Combine the positive electrode shell, negative electrode shell, positive and negative electrode sheets, diaphragm, gasket, shrapnel, and electrolyte to prepare a button battery, and test its electrochemical performance.
[0053] Depend on Figure 1 , Figure 2 It can be seen that the method adopted by the present invention has prepared carbon nanotubes and successfully doped nitrogen and nano-iron.
[0054] The performance of the lithium ion button batteries in Example 1, Example 2 and Comparative Examples 1-4 was tested respectively, and the test results are as follows:
[0055] Table 1 Electrochemical properties of lithium ion button cells prepared in Example 1, Example 2 and Comparative Examples 1-4
[0056]
[0057]
[0058] From the data in Table 1, we can see that:
[0059] (1) Under the condition of the same conductive agent content, the internal resistance of the lithium battery prepared by using the conductive agent provided by the present invention is lower, indicating that the conductive agent provided by the present invention has a better effect. The introduction of nitrogen element improves the electrochemical activity of the conductive agent, making the conductive network composed of carbon nanotubes transmit electrons faster, thereby improving the performance of the lithium battery;
[0060] (2) Under the condition of the same conductive agent content, the specific capacity and capacity retention rate of the lithium battery prepared by using the conductive agent provided by the present invention are higher, indicating that the addition of nano-iron improves the specific capacity of the lithium battery. Combining carbon nanotubes with nano-iron can not only prevent the agglomeration and volume expansion of nano-iron, but also utilize the excellent conductivity of carbon nanotubes to improve the specific capacity and capacity retention rate of the lithium battery.
Claims
1. A method for preparing nitrogen-doped carbon nanotubes loaded with nano-iron, characterized in that: The method is: (1) dissolving the catalyst in anhydrous ethanol and performing ultrasonic dispersion treatment to obtain a catalyst solution with a concentration of 0.2 to 0.6 g / L; The catalyst solution is uniformly dripped onto a designated position of the substrate, and the substrate dripped with the catalyst solution is vacuum dried to remove the solvent, thereby obtaining catalyst particles; (2) placing the substrate loaded with catalyst particles prepared in step (1) into a tubular furnace and placing it at the air inlet position of the heating zone of the tubular furnace; evacuating the tubular furnace, introducing a hydrogen-argon mixed gas, a carbon source, and a nitrogen source, turning on the heating device of the tubular furnace, and raising the furnace temperature to the reaction temperature at a heating rate of 10°C / min to prepare nitrogen-doped carbon nanotube-loaded nano-iron.
2. The preparation method according to claim 1, characterized in that: The method also includes step (3), taking out the cooled substrate from the tube furnace and immersing it in anhydrous ethanol, ultrasonically treating the substrate by an ultrasonic disperser to separate the nitrogen-doped carbon nanotube-loaded nano-iron, centrifuging the ultrasonically treated solution by a centrifuge, collecting the nitrogen-doped carbon nanotube-loaded nano-iron precipitated at the bottom, and drying it.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the catalyst is one or more of iron oxide, γ-iron oxide, ferric nitrate nonahydrate, and ferrocene.
4. The preparation method according to claim 1 or 2, characterized in that: In step (1), the substrate is one or more of a silicon wafer, nickel foam, and a quartz wafer.
5. The preparation method according to claim 1 or 2, characterized in that: In step (2), the flow rate of the hydrogen-argon mixed gas is controlled at 80-350 sccm.
6. The preparation method according to claim 1 or 2, characterized in that: In step (2), the carbon source is one or more of ethylene, acetylene, polyethylene and polypropylene.
7. The preparation method according to claim 1 or 2, characterized in that: In step (2), the nitrogen source is one or more of urea, melamine, xylene and aniline.
8. The preparation method according to claim 1 or 2, characterized in that: In step (2), the reaction temperature is 700-950° C., and the reaction time is 15-45 min.
9. The preparation method according to claim 2, characterized in that: In step (3), the drying process is vacuum drying or freeze drying.
10. An application of nitrogen-doped carbon nanotubes loaded with nano-iron prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The nitrogen-doped carbon nanotube-loaded nano-iron is used as a negative electrode conductor in a lithium-ion battery; in the negative electrode slurry, the ratio of graphite, SBR, carbon black, CMC, and nitrogen-doped carbon nanotube-loaded nano-iron is 94%: 1.8%: 2.2%: 0.5%-1%: 1%-1.5%.
Citation Information
Patent Citations
Method for preparing nanometer carbon tube on the aluminum foil
CN101139092A
Method for preparing compounds of iron nano-particles coated with carbon nano tube / graphite
CN104785777A
Iron-nitrogen-doped graphene porous material with dual-site catalytic oxygen reduction activity, and preparation method and application therefor
CN105609793A
Nitrogen-doped carbon nanotube-loaded nitrogen-doped carbon-coated iron-cobalt alloy bifunctional catalyst and preparation method and application thereof
CN110783582A
Preparation method of nitrogen-doped carbon nanotube supercapacitor
CN110957148A